2018
DOI: 10.1111/jth.14234
|View full text |Cite
|
Sign up to set email alerts
|

Flavin monooxygenase 3, the host hepatic enzyme in the metaorganismal trimethylamine N‐oxide‐generating pathway, modulates platelet responsiveness and thrombosis risk

Abstract: Background Gut microbes play a critical role in the production of trimethylamine N-oxide (TMAO), an atherogenic metabolite that impacts platelet responsiveness and thrombosis potential. Involving both microbe and host enzymatic machinery, TMAO generation utilizes a metaorganismal pathway, beginning with ingestion of trimethylamine (TMA)-containing dietary nutrients such as choline, phosphatidylcholine and carnitine, which are abundant in a Western diet. Gut microbial TMA lyases use these nutrients as substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 51 publications
2
78
0
Order By: Relevance
“…31 Further study showed that host hepatic flavin monooxygenase 3 participates in gut microbiota-dependent changes in platelet responsiveness in vivo. 32 Consistent to previous findings, a recent study found that the increase in platelet count was related to the decrease in intestinal microbial diversity and beneficial intestinal bacterial abundance. 33 Substantial evidence supports that platelet activation is highly relevant to cognitive decline.…”
Section: Discussionsupporting
confidence: 87%
“…31 Further study showed that host hepatic flavin monooxygenase 3 participates in gut microbiota-dependent changes in platelet responsiveness in vivo. 32 Consistent to previous findings, a recent study found that the increase in platelet count was related to the decrease in intestinal microbial diversity and beneficial intestinal bacterial abundance. 33 Substantial evidence supports that platelet activation is highly relevant to cognitive decline.…”
Section: Discussionsupporting
confidence: 87%
“…Table 2 The hydrogen and methane production at the end of rumen in vitro fermentation with or without the addition of TMA and NG 2 TMA, trimethylamine. 3 TMA was provided 0.69 mg/mL before fermentation. 4 ND, not detectable.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 The abundance of the 16S rRNA gene of archaea and Mmc, and CutC genes at the end of rumen in vitro fermentation with or without the addition of Choline and NG 2 Choline chloride concentration was 1.0 g/L at the beginning of fermentation. 3 CutC gene, coding choline trimethylamine lyase. Community composition of methanogens at the end of the rumen in vitro fermentation with or without the addition of TMA and NG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study first identified the critical roles of Fmo3 and Mmp19 in regulating DVT. Zhu et al (38) demonstrated that the microbe-dependent production of trimethylamine N-oxide (TMAO) contributes to the risk of thrombosis. Thus, a murine Fecl 3 -induced carotid artery injury model was established to confirm the impact of FMO3 suppression [via antisense oligonucleotide (ASO) targeting] and overexpression (as a transgene), which was examined by the plasma TMAO levels, platelet responsiveness and thrombosis potential.…”
Section: Discussionmentioning
confidence: 99%